Guess how much I love you - McBratney, Sam.; Jeram, Anita (Cambridge, Mass. : Candlewick Press, 1996)
During a bedtime game, every time Little Nutbrown Hare demonstrates how much he loves his father, Big Nutbrown Hare gently shows him that the love is returned even more.
On board pages.
Adult 690
Accelerated Reader AR
Keywords: Fathers and sons -- Juvenile fiction; Hares -- Fiction; Braille; Fathers and sons -- Fiction; Bedtime -- Fiction; Love -- Fiction